A Perceived Zone of Certainty and Uncertainty: Propositions for Research Development - Phan, Huy P.; Ngu, Bing H. (Frontiers in Psychology, 2021)
Possessing expert schemas is a positive feat that may yield a number of adaptive outcomes (e.g., informing procedural understanding that may result in the skipping of solution steps). Limited schemas, in contrast, may deter a novice’s progress, limiting his/her capability to flourish. Taken as a whole, it may be concluded that expert schemas are more advantageous than novice schemas, differentiating learners in terms of expert and novice. Having said this, more recently, researchers have argued that possessing expert schemas could serve as a deterrence. In his published article, Dane (2010) described a concept known as cognitive entrenchment, which is defined as a high level of stability in one’s domain schemas. This description interestingly suggests that ‘entrenchment’ or ‘situated fixation’ of a subject matter would hinder a person’s learning experience, namely – his/her inability and/or unwillingness to adapt to a new context, and/or his/her inflexibility and insistence to stay on course without any intent to change. One example of cognitive entrenchment is related to professional football, wherein it has been argued that some football coaches are cognitively entrenched within their expert schemas, resulting their demised gameplans and strategic acumens. We advance the study of cognitive entrenchment by proposing an alternative viewpoint, which we term as the ‘perceived zone of certainty and uncertainty’. This proposition counters the perspective of cognitive entrenchment by arguing that it is a person’s cognitive appraisal, judgment, mental resolute, and determination in certainty of his/her success or failure, or the uncertainty of success or failure, that would explain the notion of inflexibility and/or unwillingness to adapt, and/or insistence to stay on course without any attempt to deviate. Moreover, we rationalize that certainty of success or failure would closely associate with a person’s feeling of comfort, whereas uncertainty would associate with his/her feeling discomfort. In this analysis, we strongly believe that willingness to change and adapt, reluctance and insistence to remain on course, and/or inclination to embrace flexibility may not necessarily relate to the concept of cognitive entrenchment (Dane, 2010, 2011); rather, inflexibility, and/or reluctance to change for the purpose of adaptation, has more to do with a person’s